An energy-efficient integration of a digital modulator and a Class-D amplifier - Zia, Muhammad Yousuf Irfan; Tierno, Raúl; Luque-Nieto, Miguel Ángel; Otero-Roth, Pablo (MDPI, 2020)
Energy consumption is always a key feature in devices powered by electric accumulators. The power amplifier is the most energy-demanding module in mobile devices, portable appliances, static transceivers, and even nodes used in underwater acoustic networks. These devices incorporate a modulator, typically a pulse-width modulation (PWM) and a class-D power amplifier, for higher efficiency. We propose a technique to integrate the modulator of a transmitter and PW-modulator of a class-D amplifier to improve the overall efficiency of the system. This integrated set operates as an up-converter, phase modulator (PM), and binary phase-shift keying (BPSK) modulator under certain conditions. The theoretical concept is verified using Matlab and a model is designed and simulated in Simulink. For validation purposes, an electronic circuit is built and tested using Multisim. The results obtained by simulations and circuit implementation show that the proposed integrated system is an energy-efficient and cost-effective solution compared to conventional techniques.
Keywords: Modulación por impulsos codificados; Amplificadores (Electrónica) - Consumo de energía; BPSK; QPSK; PWM; Class-D amplifier; Power efficiency; Digital modulator